PENGARUH TINGKAT KEMISKINAN DAN PENDAPATAN PERKAPITA TERHADAP PENERIMAAN PAJAK DAERAH SERTA OPINI AUDIT DENGAN TINGKAT KEPERCAYAAN MASYARAKAT SEBAGAI VARIABEL INTERVENING TERHADAP PENERIMAAN PAJAK DAERAH PEMERINTAH PROVINSI SE-INDONESIA - Alwi, Muh; Su'un, Muhammad; Amiruddin, Amiruddin (Economos : Jurnal Ekonomi dan Bisnis, 2021)
This study aims: To investigate whether the Poverty Level Affects Provincial Tax Revenues in Indonesia, to test whether per capita income affects provincial tax revenue in Indonesia, to test whether the Audit Opinion with Intervention Variables, Public Trust Level, to test whether the Audit Opinion affects Provincial Tax Revenues in Indonesia. This academic study typically uses secondary data with time series data for the period 2010, 2012, 2014, 2016, and 2018. The data analysis technique typically uses the stimulus equation with the path analysis estimation technique. The Statistical Package for the Social Science application program (SPSS) version 23 is typically used to carefully help carefully analyze the data typically used in this study. The results showed that: The level of poverty has a significant effect on Provincial Tax Revenues in Indonesia, Per capita income has no significant impact on Provincial Tax Revenues in Indonesia, Audit Opinion with Intervening Variables Community Trust Level typically has a significant effect on Provincial Tax Revenues in Indonesia.